A phase Ib study to assess the safety of the human papillomavirus DNA vaccine (AMV002) in combination with durvalumab for HPV-associated oropharyngeal squamous cell carcinoma - Ladwa, Rahul; Chandra, Janin; Woo, Wai-Ping; Finlayson, Neil; Liu, Howard; McGrath, Margaret; See, Adrienne; Hughes, Brett G.; Cooper, Caroline L.; Jackson, Jim E.; Dzienis, Marcin; Xu, Yan; et al. (Frontiers in Oncology, 2024)
Programmed cell death ligand 1 (PD-L1) inhibitors have limited efficacy as monotherapy in patients with recurrent/ metastatic (R/M) Human Papilloma Virus (HPV) oropharyngeal squamous cell carcinoma (OPSCC). A phase I study of the therapeutic HPV-16 DNA vaccine AMV002 in curatively treated patients with OPSCC demonstrated a measurable immune response against HPV while being associated with high safety and tolerability. This prospective phase Ib single centre pilot study aims to test the safety and tolerability of combined PD-L1 inhibitor, Durvalumab, with AMV002 in 12 patients with recurrent OPSCC.Participants had evidence of R/M HPV-associated OPSCC. They received three intradermal administrations of AMV002 with Durvalumab followed by Durvalumab maintenance. Safety and tolerability data was the primary endpoint. The study was conducted with ethical approval (HREC/2018/QMS/47293) in Brisbane, Australia.The most common adverse event (AE) related to vaccine administration was erythema at the injection site. There were no grade 3 or 4 vaccine related AEs. There was one presumed immune-related grade 3 elevation in lipase secondary to Durvalumab with no intervention required. No patient ceased study due to treatment-related AEs. At week 16, objective response rate was 8% (N=1) and disease control rate was 17% (N=2). At a median follow up of 25.6 (20.0-26.6) months there was one long term complete response while all other participants developed progressive disease. Of the 11 evaluated patients, 9, (82%) had E6 and/or E7specific T cell responses to the vaccine.